DETECTION OF CITRUS VEIN PHLOEM DEGENERATION (CVPD) DISEASE BY POLYMERASE CHAIN REACTION (PCR) AND PROTEIN ANALYSIS USING SDS PAGE (A Review) - Wirawan, I Gede Putu; Julyasih, Ketut Srie Marhaeni (International Journal of Biosciences and Biotechnology; Vol 3 No 1 (2015))
Citrus Vein Phloem degeneration (CVPD) is the most important disease and a major cause of yield loss citrus plantations in almost all countries, especially Asia and Africa. CVPD disease is caused by gram negative bacteria, Liberobacter asiaticum L. Pathogens can not be cultured in vitro, but can be detected by PCR using 16S rDNA fragment as a primer and by electron microscopy. The use of PCRusing specific primer pair can detect infected plants more accurately. Citrus plant that infected by CVPD disease contain a very specific protein that produced by the pathogen. The specific protein molecules can be detected by comparing the protein bands of infected citrus plants and the healthy one which have molecular weight of approximately 16 kDa and 66 kDa, whereas in healthy citrus plant that protein molecule was not found.
Keywords: Citrus Vein Phloem Degeneration, Polymerase Chain Reaction, SDS-PAGE